PSYCHODIAGNOSTIC OF AUTISM SPECTRUM DISORDER IN AN ADULT FEMALE PATIENT - Freitas de Oliveira, Miria Caroline (2025)
This case report aimed to provide reflections and assess the impacts of a late diagnosis of Autism Spectrum Disorder on mental health and quality of life in adulthood. It is a case study with a quantitative and qualitative approach, of exploratory, descriptive, and cross-sectional nature. The case observation was conducted at a psychology course training clinic. The study was carried out with a female participant, aged 20, with a hypothesized diagnosis of Autism Spectrum Disorder, who was monitored throughout 2023 by a psychology intern. The following instruments were used for data collection: adult anamnesis, social responsiveness scales, social skills inventory, clinical interview based on the DSM-V-TR diagnostic criteria, nonverbal general intelligence test, executive function test, and a semi-structured interview. The results highlighted significant challenges in the participant's social and emotional adaptation, as well as the importance of diagnosis in developing support and development strategies. It is concluded that the late identification of Autism Spectrum Disorder can impact various aspects of adult life, emphasizing the need for early interventions and continuous support to promote well-being and quality of life.